Activation of neutrophils by testosterone in Behçet's disease - (:unkn) unknown (My University, 2007)
Objective. Gender differences, especially in disease severity, are observed in Behçet's disease (BD), a systemic vasculitis of unknown etiology. To determine the putative role of testosterone on neutrophil activity exhibited by patients with BD, peripheral blood neutrophils were examined in vitro before and after treatment with testosterone. Methods. Peripheral blood neutrophils of 49 patients with BD (26M:23F), 33 patients with ankylosing spondylitis (AS) (23M:10F), 8 female patients with hirsutism and 31 healthy individuals (19M:12F) were analyzed by flow cytometry. Neutrophil-ROS-generating capacity, anti-CD66b, anti-CD16, Phi-philux and PI staining techniques were used for evaluating neutrophil activation and apoptosis. Results. Gender differences were striking not only in the mean oxidative burst response but also in the rate of apoptosis. Male BD patients manifested increased burst response before testosterone treatment compared with females (8.0 ± 4.9 vs. 4.9 ± 3.3, p < 0.01). Consistent with oxidative burst results, baseline percentages of CD66b (99.1 ± 0.9 vs. 94.7 ± 5.3p < 0.04) and CD16 expressing cells were greater in male BD patients. A decreased apoptosis ratio was observed using phiphilux and PI staining in BD patients. This was especially significant in male compared to female BD patients (2.4 ± 1.4 vs. 6.8 ± 5.8, p < 0.002). BD itself rather than the gender was found to be the most important predictor of this altered apoptosis ratio in BD determined by linear regression analysis. Conclusion. Our results suggest that a contribution of testosterone to the BD pathogenesis cannot be ruled out. However, causative factors for disturbed apoptosis especially seen in male BD patients need to be further evaluated. © Copyright Clinical and Experimental Rheumatology 2007.
Keywords: Apoptosis; Behçet's disease; Neutrophil functions; Sex hormones